Exploring Women Empowerment: Dried-grass Weavers in South Kalimantan - Sari, Faizah; Yudianto, B. Realino; Tauryawati, Mey Lista; Sampe, Maria Z. (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2024)
The paper underscores challenges and opportunities in the community of female dried-grass basket weavers in Purun Village, Banjarbaru, South Kalimantan, Indonesia. A training workshop based on how to improve the branding effort using online shops was conducted through a community classroom-type presentation with a simple step-by-step procedure, a practice for taking a product photograph from a smartphone, and a demonstration of setting up an online shop. Fourteen female weavers of Purun Village, Banjarbaru, South Kalimantan, Indonesia participated in the workshop. Results show a set of characteristics of a female basket weaver that uncovers both challenges and opportunities for improvement, not only for the individual woman but also the community and product sustainability of dried-grass basket weaving. Implications for continuous interaction and future research were discussed, including (1) the importance of understanding a variety of women’s roles in private and public spheres within the community context that could complement each other, and (2) the inevitability of introducing technology to the community to help furthering the participant’s skills and of small business community.